Kinetics IgM and IgG SARS-CoV-2 in Recovery patients with Negative Evaluation RT-PCR - Endang, Jusup; Sariyanti, Mardhatillah; Triana, Dessy; Rizqoh, Debie; Enny, Nugraheni (UNUSA Press, 2023)
Background: Coronavirus is the major pathogens at human respiratory system. The antibody is a response infected patients largely not clearly. We need to understanding of antibody responses to great diagnosis and treatment studies. Objective: In this article the objective is to describe that kinetics of IgM and IgG SARS-CoV-2 in recovery patients. Method: Cohort study used a total 19 subjects who had negative evaluation RT-PCR after confirmed. IgG and IgM of SARS-CoV-2 were detected by IFA (Immuno fluorosence assay) used serum. Serum were collected 3 times after 1 month, 2 month and 4 month negative evaluation RT-PCR We profiled the serological responses (IgM and IgG) to SARS-CoV-2. Result: Majority the IgM SARS-CoV-2 post evaluation RT-PCR were very low after 1,2,4 month negative evaluation. IgG SAR-CoV-2 patients post negative evaluation RT-PCR decreased after 4 months. The level IgM and IgG level increase at first week and decrease after 12 weeks. Conclusion: IgM level lower than IgG level overtime. Quantitative IgG and IgM detection could be point of diagnosis and manifestation.